Biochar enhanced soil aggregation and C‐related enzyme activity in post‐mining land on the Loess Plateau, China. (21st March 2022) - Yan, Meifang; Li, Xiari; Liu, Yang; Li, Yan; He, Linru; Zhang, Jianbiao
Abstract: Soil organic carbon in aggregates of different size classes varies greatly in stabilization and resistance, and its mineralization depends highly on enzyme activity within aggregates. However, the dynamics of enzyme activities in response to aggregate turnover remain unclear. In this study, we explored four soil enzymes within different aggregates (>2, 2–0.25, 0.25–0.053, and <0.053 mm) in a biochar‐addition (1%, 3%, and 5%, respectively) experiment in post‐mining land. Soil aggregate size had significant effects on β‐glucosidase (BG) and urease (UR) ( p  < 0.01), and the enzyme activities were significantly higher in macroaggregates (>0.25 mm) than in microaggregates (<0.25 mm). Biochar addition increased the proportion and stability of macroaggregates. Moreover, BG, UR, and peroxidase activities were significantly stimulated across all aggregate fractions in treatment of 5% addition, increasing by 134.6%, 163.6%, and 35.7%, respectively ( p  < 0.01), while alkaline phosphatase activity in macroaggregates decreased by 45.8% compared with that in the control. In macroaggregates, higher enzyme activities were closely correlated with the increase of easily oxidized carbon ( p  < 0.01) due to biochar addition, and the increase in nitrogen content was also beneficial to promote microbial growth and activity. Our study suggests that biochar addition may improve soil structure and nutrient status, which would accelerate the recovery of microbial function in degraded lands.